Pengaruh Shalat Dhuha Terhadap Kecerdasan Emosional Siswa Kelas VIII SMP IT Al-Kaffah Kota Binjai - Putri Zahara Nst; Hemawati Hemawati; Rabitah Hanum Hasibuan (Departement of Mathematics Education, 2024)
Intelligence is a person's ability to recognize, understand, manage and express emotions well. Dhuha prayer, as a sunnah prayer performed in the morning, has been proven to have a positive impact on students' emotional intelligence. Through Duha prayer, students are taught to increase self-awareness, control negative emotions, and increase empathy towards others. The research methodology is quantitative research. In this research, the population is all class VIII students of SMP IT Al-Kaffah Binjai for the 2023/2024 academic year, in this case there are two classes, namely VIII-A and VIII-B. The total number of class VIII students is 32 people. Sampling for this research used the total sampling technique. In accordance with the number of students in class VIII, namely 32 people, the sample in this study will be 32 students. The results of the discussion are that there is an influence between Duha prayer on students' emotional intelligence with a coefficient value (R Square) = 0.752 indicating that the influence of Duha prayer on students' emotional intelligence is 0.752 or 75.2%, in the range of 0.60-0.799. and is in the strong category.‎